Treatment of congenital epulis (granular cell tumour) with excision and gingivoperiosteoplasty - Narasimhan, Kailash (Pulsus Group Inc, 2007)
Congenital epulis, or granular cell tumour, is a rare, benign intraoral tumour present on the mucosa of the alveolar ridge, with the potential to interfere with respiration and feeding. Treatment involves surgical excision, and recurrences are rare. The management of the alveolar deficiency associated with this tumour has not previously been addressed. In the present report, a patient with a typical epulis, treated surgically with excision and extrapolation of Millard’s gingivoperiosteoplasty technique to reconstruct the associated alveolar defect with restoration of alveolar ridge continuity, is presented. The differential diagnosis and complications of this tumour are discussed.